2014
DOI: 10.1007/s10517-014-2732-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glutathione-S-Transferase M1 (GSTM1) and T1 (GSTT1) Genes in the Development and Progress of Chronic Myeloid Leukemia and in the Formation of Response to Imatinib Therapy

Abstract: The effects of GSTM1 and GSTT1 gene deletion ("zero") polymorphisms on the risk of chronic myeloid leukemia development and progress and on response to imatinib monotherapy were studied in the representatives of the Russian nationality in the Vyatka region of Russia. Homozygotic carriership of GSTT1 "zero" allele was associated with a 3.66 times higher risk of chronic myeloid leukemia development in residents of the Vyatka region (OR=3.66, 95% CI=2.12-6.30; p<0.0001). Combinations of the "zero" GSTM1 and GSTT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The meta-analysis carried out by He et al showed that the deletion of both alleles of GSTT1 increases the risk of chronic lymphocytic leukemia [ 9 ]. Furthermore, double null genotype of GSTM1 and GSTT1 may be associated with the development of chronic lymphocytic leukemia [ 9 , 42 , 43 ].…”
Section: Glutathione S-transferasesmentioning
confidence: 99%
“…The meta-analysis carried out by He et al showed that the deletion of both alleles of GSTT1 increases the risk of chronic lymphocytic leukemia [ 9 ]. Furthermore, double null genotype of GSTM1 and GSTT1 may be associated with the development of chronic lymphocytic leukemia [ 9 , 42 , 43 ].…”
Section: Glutathione S-transferasesmentioning
confidence: 99%